2021
DOI: 10.1186/s42834-020-00075-3
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle analysis of potential municipal solid wastes management scenarios in Tanzania: the case of Arusha City

Abstract: The municipal solid wastes (MSW) management technologies in most cities of developing countries pose a continuous risk of contaminating the environment and affecting human health adversely; often because MSW technologies are not comprehensively analyzed before their implementation. For this purpose, the life cycle assessment methodology was applied to access the different MSW management scenarios in Arusha City, Tanzania. Three different scenarios of recycling and sanitary landfilling (RSL) were developed as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 28 publications
3
16
0
1
Order By: Relevance
“…This increase is attributed to the introduction of various MSW valorization streams throughout the scenarios. Many researchers have found that the less amount of MSW is landfilled, due to MSW treatment activities’ introduction, the less negative environmental impact is observed [ 46 , 47 , [55] , [56] , [57] ]. In this study, landfill diversion rates increase because the burden on the landfilling decreases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase is attributed to the introduction of various MSW valorization streams throughout the scenarios. Many researchers have found that the less amount of MSW is landfilled, due to MSW treatment activities’ introduction, the less negative environmental impact is observed [ 46 , 47 , [55] , [56] , [57] ]. In this study, landfill diversion rates increase because the burden on the landfilling decreases.…”
Section: Resultsmentioning
confidence: 99%
“…In Nottingham (England), for example, results from LCA indicated an improvement in greenhouse gas reduction while improving waste collection, treatment, and material recycling [ 55 ]. Furthermore, in Arusha (Tanzania), LCA results revealed that a combination of recycling, composting, and landfill performed better in alleviating environmental impacts [ 56 ]. This underlines the importance of conducting such studies in the waste management sector to induce evidence-based decision-making and efficiently contribute to improving the MSW field.…”
Section: Methodsmentioning
confidence: 99%
“…Another interesting work of Richard et al [ 21 ] investigated the economic cost and environmental burdens in municipal solid wastes (MSW) management. Compared to the other scenarios, one of the solutions, which is a combination of recycling, composting, and landfilling, had the lowest economic cost and environmental impact in most categories.…”
Section: Discussionmentioning
confidence: 99%
“…It was used as a functional unit in six studies. 14,16,17,19,20 Two studies used one metric ton of waste, 22,26 and some studies used one kg of waste. 15,18 Yong used 1000 kg of collected end-of-life phones, 24 excluding batteries.…”
Section: Functional Unitmentioning
confidence: 99%